Case Report: The application of metagenomic next generation sequencing in diagnosing fungal malignant external otitis: a report of two cases - Wang, Qi; Hu, Rui; Zhu, YiFan; Zhu, WenQing; Jiang, Hua (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Most of malignant external otitis (MEO) cases reported in the literature are attributed to Pseudomonas aeruginosa. Fungal infections in MEO are also likely but extremely rare. And conventional microbiology tests is diffificult to diagnose. Case description: Two patients were diagnosed with Fungal malignant external otitis (FMEO) due to Aspergillus by metagenomic Next-Generation Sequencing (mNGS) and recovered after comprehensive treatment including operation and voriconazole. The antifungal treatment was delayed due to repeated cultures of secretions were negative and pathological examination showed granulation tissue proliferation with extensive neutrophil infiltration.Conclusion: mNGS might be helpful for patients suspected with FMEO, especially when conventional microbiology tests were negative.